Association of Maternal Depression During Pregnancy and Recent Stress With Brain Age Among Adult Offspring - Mareckova, Klara; Marecek, Radek; Jani, Martin; Zackova, Lenka; Andrýsková, Lenka; Brazdil, Milan; Nikolova, Yuliya S (JAMA network open, 2023)
IMPORTANCE: Maternal mental health problems during pregnancy are associated with altered neurodevelopment in offspring, but the long-term relationship between these prenatal risk factors and offspring brain structure in adulthood remains incompletely understood due to a paucity of longitudinal studies. OBJECTIVE: To evaluate the association between exposure to maternal depression in utero and offspring brain age in the third decade of life, and to evaluate recent stressful life events as potential moderators of this association. DESIGN, SETTING, AND PARTICIPANTS: This cohort study examined the 30-year follow-up of a Czech prenatal birth cohort with a within-participant design neuroimaging component in young adulthood conducted from 1991 to 2022. Participants from the European Longitudinal Study of Pregnancy and Childhood prenatal birth cohort were recruited for 2 magnetic resonance imaging (MRI) follow-ups, one between ages 23 and 24 years (early 20s) and another between ages 28 and 30 years (late 20s). EXPOSURES: Maternal depression during pregnancy; stressful life events in the past year experienced by the young adult offspring. MAIN OUTCOMES AND MEASURES: Gap between estimated neuroanatomical vs chronological age at MRI scan (brain age gap estimation [BrainAGE]) calculated once in participants' early 20s and once in their late 20s, and pace of aging calculated as the differences between BrainAGE at the 2 MRI sessions in young adulthood. RESULTS: A total of 260 individuals participated in the second neuroimaging follow-up (mean [SD] age, 29.5 [0.6] years; 135 [52%] male); MRI data for both time points and a history of maternal depression were available for 110 participants (mean [SD] age, 29.3 [0.6] years; 56 [51%] male). BrainAGE in participants' early 20s was correlated with BrainAGE in their late 20s (r = 0.7, P < .001), and a previously observed association between maternal depression during pregnancy and BrainAGE in their early 20s persisted in their late 20s (adjusted R2 = 0.04; P = .04). However, no association emerged between maternal depression during pregnancy and the pace of aging between the 2 MRI sessions. The stability of the associations between maternal depression during pregnancy and BrainAGE was also supported by the lack of interactions with recent stress. In contrast, more recent stress was associated with greater pace of aging between the 2 MRI sessions, independent of maternal depression (adjusted R2 = 0.09; P = .01). CONCLUSIONS AND RELEVANCE: The findings of this cohort study suggest that maternal depression and recent stress may have independent associations with brain age and the pace of aging, respectively, in young adulthood. Prevention and treatment of depression in pregnant mothers may have long-term implications for offspring brain development.
Keywords: dospělí; Female; dítě; Adult; mladý dospělý; ženské pohlaví; longitudinální studie; lidé; těhotenství; zpožděný efekt prenatální expozice; mozek; kohortové studie; Cohort Studies; dospělé děti; Male; Brain; Young Adult; Prenatal Exposure Delayed Effects; Adult Children; Child; deprese; mužské pohlaví; Pregnancy; Depression; Longitudinal Studies; Humans